Antipresuppositions, logophors and shifted indexicality - Blunier, David (Proceedings of the Amsterdam Colloquium, 2022)
Some languages can ‘shift’ indexicals, such as I and you, and use them anaphorically to refer to participants of the speech event being reported (Schlenker 2003, Deal 2020); other languages use dedicated ‘logophoric’ pronouns in the same fashion. A fact about logophoric languages is that, in speech reports, the use of a 3rd person form to refer to the author of the report is prohibited, giving rise to a disjointness or ‘anti-coreference’ effect. An interesting observation that has often gone unnoticed in the previous literature is that the same generalization holds for languages displaying obligatory indexical shift, suggesting that the two phenomena should be given a uniform account. I argue that this type of ‘reporting disjointness’ stems from the computation of an antipresupposition at level of person features (Percus 2006, Sauerland 2008a i.a.). Altogether with the aforementioned generalization, the present proposal is shown to be able to correctly derive distribution patterns of both classes of pronouns across languages.